Climate Policy and Optimal Public Debt - Maximilian Kellner; Marco Runkel (Center for Economic Studies and Ifo Institute (CESifo), 2021)
This paper analyzes the optimal level of public debt when taxes are used not only for funding public expenditures but also for correcting externalities from climate change. Taking into account externalities implies that the optimal policy deviates from tax smoothing. Provided cumulative marginal damages are larger from today's than from tomorrow's emissions, the internalization of externalities decreases [increases] optimal debt if tax rates are on the increasing [decreasing] side of the Laffer curve. The reversed holds if the cumulative marginal damages increase over time. Allowing for endogenous adaptation investments reduces the deviation from tax-smoothing, but nevertheless increases optimal debt.
Keywords: H23; H63; Q54; Q58; 330; environmental externality; public debt; tax smoothing